2022
DOI: 10.3390/medicina58030399
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Hospitalized COVID-19 Patients with History of Atrial Fibrillation

Abstract: Background and objectives: Pre-existing atrial fibrillation (AF) is a frequent comorbidity in hospitalized patients with COVID-19; however, little is still known about its prognostic role in infected patients. The aim of our study was to evaluate whether the pre-existing AF as comorbidity would contribute to increase the risk for severe forms of COVID-19, worse prognosis, or even higher mortality. Materials and Methods: We retrospectively evaluated all consecutive COVID-19 patients admitted to the emergency de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…In their study, AF was associated with an increased risk of severe ARDS, but it did not affect the risk of death. The type of pre-existing AF did not impact the outcome [10]. Finally, in a US study, Kuno et al found that in-hospital mortality was not signi cantly different in patients with anticoagulation before admission compared to those without [11].…”
Section: Introductionmentioning
confidence: 93%
“…In their study, AF was associated with an increased risk of severe ARDS, but it did not affect the risk of death. The type of pre-existing AF did not impact the outcome [10]. Finally, in a US study, Kuno et al found that in-hospital mortality was not signi cantly different in patients with anticoagulation before admission compared to those without [11].…”
Section: Introductionmentioning
confidence: 93%